TEKNOLOGI BIOFLOK (BFT) SEBAGAI TEROBOSAN USAHA PENDEDERAN IKAN GABUS (Channa striata Bloch, 1793) - Sihananto, Bambang; Supriyono, Eddy; Diki, Diki (EnviroScienteae, 2023)
Environmental issues related to aquaculture have recently surfaced, especially related to the use of natural resources such as water and land use including the price of feed which is increasingly expensive, biofloc technology is able to answer these problems by using less water, land, and commercial feed compared to conventional methods. The purpose of this study was to evaluate and take strategic steps to utilize biofloc technology in the snakehead fry nursery business. Data and information were collected through interviews using questionnaires prepared using the analytic hierarchy process (AHP) approach, strength weakness opportunities threat (SWOT) analysis, and business analysis was conducted to determine the potential for business development. This study was conducted using two types of rearing containers: round tarpaulin tubs with a diameter of 3 m and plastic containers. The business of rearing snakehead fry using the biofloc method both in plastic containers and in round tarpaulin tanks in one cycle shows inefficient results (<1). The criteria of yield, cost, growth, feed and water are the criteria used as the basis for assessing the effective and efficient business of snakehead fry rearing with a higher alternative weight of the biofloc method (0,629) when compared to conventional (0,371). Through SWOT analysis, the use of less feed and water is the strength of the biofloc method in the cork fish seed breeding business.